TiO2–x Based Nanoplatform for Bimodal Cancer Imaging and NIR-Triggered Chem/Photodynamic/Photothermal Combination Therapy - Guo, Wei; Wang, Fei; Ding, Dandan; Song, Chuanqi; Guo, Chongshen; Liu, Shaoqin (Chemistry of materials, 2017)
Integration of cancer diagnosis and treatment, namely theranostics, is an important issue in the biomedical field. Benefiting from an excellent photothermal effect, ROS generation ability, and the desired mesoporous structure of the TiO2–x matrix, we strategically designed and fabricated a TiO2–x based theranostic system for realizing fluorescence/photoacoustic tomography (PAT) bimodal imaging guided triple therapy for photothemal/photodynamic/chemotherapy in this work. Nonstoichiometric TiO2–x nanospheres are excellent near-infrared absorptive material, which takes on both photosensitizer and photothermal agent roles in implementing PDT/PTT combination therapy and PAT imaging. Moreover, the mesoporous structure of TiO2–x also allowed drug loading, and the polydopamine sealing layer enabled it to induce NIR/pH-triggered drug controlled release. Resultantly, both the in vitro and in vivo experiment manifested the remarkable tumor inhibition and tumor imaging effects by the TiO2–x based theranostic system. The antitumor mechanism was attributable to a synergistic therapeutic effect (combination index = 0.318) of DOX-induced DNA damage, and PDT/PTT caused mitochondrial dysfunction and a change in the cell membrane permeability. Innovatively, the B-mode ultrasonography was adopted to monitor the rehabilitation process at the solid tumor site after treatment, which observed a liquefaction necrosis process.